Systematic studies in Turnera (Turneraceae). III. Series Anomalae and Turnera - María Mercedes Arbo (Bonplandia, 2005)
Turnera L. is arranged in 9 series. In this paper the revision of the species with floral nectar pockets is presented: series Anomalae Urb. and series Turnera. Within the latter 2 subseries are proposed, Turnera and Umbilicatae Arbo, differenciated upon morphology and cytogenetics. Series Anomalae has racemose inflorescences, the peduncle free or attached to the petiole, or sometimes lacking; series Turnera has 1-flowered epiphyllous inflorescences. Series Anomalae includes 14 species which live between 02-24ºS and 35-65ºW, in the Amazonian and Chaco forests, the following being new: T. amazonica, T. discors, T. involucrata, T. kuhlmanniana, T. laciniata, T. reginae, T. sancta and T. bahiensis var. truncata. Subseries Umbilicatae lives in Bahia and surroundings, up to 1600 m, it has 8 species being new T. coriacea var. solium. Subseries Turnera has a distribution similar to that of the genus as a whole, in a variety of environments; it has 19 species, 3 being new: T. campanulata, T. fernandezii and T. occidentalis; several species are weedy, 2 having reached the Old World. Keys, illustrations and distribution maps are provided.